Food Allergy Awareness Among Kitchen and Service Staff in Food Businesses: A Study in Kütahya and Afyonkarahisar Provinces - Zeynep ŞİMŞEK; Medine DOĞAN (ISPEC Journal of Agricultural Sciences)
Nutrition is one of the most fundamental rights of individuals. However, some foods can cause various symptoms in individuals' digestive and immune systems. Another factor that causes symptoms is the difficulty in digesting or absorbing certain food components. Consumption of such foods can sometimes cause mild symptoms, but it can also lead to serious or even fatal consequences. Individuals with foodborne illnesses should report their condition to businesses and receive information from service and kitchen personnel. Business personnel should be trained on this issue in order to inform customers. Kitchen personnel in businesses should prepare meals meticulously, and business owners should include information on these issues in their menus. Businesses should provide customers with an information text or service personnel that includes information about allergens in their products. The main question of this research is "What are the perceptions of food and beverage business employees towards individuals with food allergies?" is the question. This study aims to examine the level of care that businesses show towards consumers with food allergies in their kitchen practices. The analysis of the data was interpreted by evaluating the arithmetic averages of the participants' responses to each question on a 5-point Likert scale. In the study, 128 food business employees were surveyed using a 5-point Likert scale consisting of questions determined by the researchers as a result of the literature review. Participants were asked 12 general and 5 specific questions. As a result of the study, the question with the highest value with an average of 4.2188 was "Do you think that you can do your best to avoid causing harm to consumers who encounter an allergic situation in kitchen applications?" This finding proves that business employees are ready to do their best not to victimize individuals with food allergies in problems encountered in businesses related to food allergies.